PENGARUH KEKERASAN BAJA ST.60 DALAM PROSES CARBURIZING DENGAN PENAMBAHAN SERBUK KARBON, ANTRASIT, ARANG KAYU YANG DI IKUTI PENDINGINAN CEPAT - Deden Arafah Deden; Somawardi Somawardi (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
This study aims to obtain the required hardness values as a result of the heat treatment process with the addition of carbon powder, anthracite, and wood charcoal followed by rapid delayan and examine the effect of rapid cooling with variations in cooling and the addition of carbon powder, wood charcoal, and anthracite. The materials used in this study were ST.60 steel in the form of selinders, then anthracite media, wood charcoal and carbon powder. Specimens are treated with heat treatment with a temperature of 600°C - 900°C with a containment time of 30 minutes-90 minutes. Then done quenching with sea water cooling media, plain water, ice water and oil. After that, a three-point hardness test was conducted on the surface of the specimen and the test was conducted with Hardness Testing Machines Limited hardness test equipment with Type 8150 LK (United Kingdom). And the method performed is Complete Random Design. From the test results were obtained the required hardness value is in the active karbn media 63.06 HRC by using ice water cooling media and followed by wood charcoal with a hardness value of 54.33 HRC with sea water cooling media while anthracite media hardness value of 52.76 HRC with sea water cooling media. High hardness values are affected by low cooling viscosity and small carbonated material dimensi.